Tobramycin, amikacin, sissomicin, and gentamicin resistant Gram-negative rods. Issue 6047 (27th November 1976) - Drasar, F A; Farrell, W; Maskell, J; Williams, J D
Abstract : Sensitivities to gentamicin, sissomicin, tobramycin, and amikacin were compared in 196 gentamicin-resistant Gram-negative rods and in 212 similar organisms sensitive to gentamicin, mainly isolated from clinical specimens. Amikacin was the aminoglycoside most active against gentamicin-resistant organisms, Pseudomonas aeruginosa, klebsiella spp, Escherichia coli, Proteus spp, Providencia spp, and Citrobacter spp being particularly susceptible. Most of the gentamicin-resistant organisms were isolated from the urine of patients undergoing surgery. Gentamicin was the most active antibiotic against gentamicin-sensitive E coli, Proteus mirabilis, and Serratia spp. Pseudomonas aeruginosa and other Pseudomonas spp were most susceptible to tobramycin.